Measuring ethnocultural empathy in Japanese undergraduates: the validity and reliability of the Japanese version of the scale of ethnocultural empathy - Ostman, David; Xethakis, Larry (Frontiers in Education, 2024)
IntroductionThe purpose of this study was to adapt the English version of the Scale of Ethnocultural Empathy (SEE) for use in the Japanese context and to determine the validity and reliability of the adapted version to allow for the measurement of cultural empathy and promote further research into this concept in Japan. The SEE is a widely-used measure of cultural empathy which has been adapted for use in a number of cultures (e.g., Turkish, Swedish, Spanish), however the validity and reliability of this scale in the Japanese context has yet to be determined. While recognition of the importance of learner empathy in intercultural interactions has increased, at present, a validated scale to measure ethnocultural empathy has not been presented.MethodsResponses from 777 Japanese undergraduate students were used to determine the construct validity of the SEE using exploratory and confirmatory factor analysis, as well as to assess the convergent validity of the scale using the Interpersonal Reactivity Index (IRI). Reliability was evaluated using Cronbach’s alpha and test-retest validity.ResultsFactor analysis revealed two factors underlying the Japanese version of the SEE (SEE_J), explaining 42.1% of variance. The two factors—Empathic Feeling and Expression (EFE_J) and Empathic Awareness and Perspective Taking (EAPT_J)—were moderately correlated. Correlations between the SEE_J, EFE_J and EAPT_J with two subscales of the IRI provided evidence of convergent validity. The SEE_J, EFE_J and EAPT_J displayed sufficient internal and test-retest reliability. Respondents reported significantly higher levels of EFE_J than EAPT_J, and women reported significantly higher SEE_J and EFE_J than men, both of which are similar to the results of past studies using the SEE in other cultural contexts.DiscussionThe validation of the SEE_J allows for the measurement of cultural empathy and further research into this concept in the Japanese context, as well as the development of programs to enhance ethnocultural empathy in areas where Japanese individuals come into contact with individuals from other cultures, such as counseling, healthcare and education.